Increasing the Red Fraction in Light-emitting Diode Supplemental Light Enhances Yield Without Affecting the Quality of Greenhouse-grown Lettuce (Lactuca sativa L.) - Annalisa Somma; Ying Liu; Lorenzo B.A. Nielen; Sebastian Olchowski; Ep Heuvelink; Leo F.M. Marcelis (HortScience)
Supplemental lighting by light-emitting diodes (LEDs) in a greenhouse allows for spectral flexibility, which may enhance plant growth and morphology, yield, quality, light use efficiency, and electric energy efficiency (yield/kWh). A greenhouse experiment of two lettuce (Lactuca sativa L.) cultivars (green-leaved and reddish-leaved) grown under four supplemental LED light spectra at a photosynthetic photon flux density of 200 μmol·m−2·s−1 and containing 38%, 63%, 81%, or 95% red photons (red fraction) in combination with blue, green, and far-red wavebands was conducted. Yield and growth parameters, like the total plant biomass, increased linearly with an increasing red fraction for both cultivars. In general, spectral effects were stronger in the reddish-leaved cultivar, in which leaf fresh weight increased by 35% compared with only 10% in the green-leaved cultivar. The red fraction barely affected lettuce quality (pigment, total phenolic compounds, vitamin C, total soluble sugar, starch, and mineral composition). The results indicated that a high red fraction in supplemental LED light enhances lettuce yield, light use and energy efficiency, and yield per kWh while preserving quality.